Hypertrophic osteopathy associated with renal pelvis transitional cell carcinoma in a dog - Grillo, Thais P. [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Mamprim, Maria J. [UNESP]; de Jesus, Carlos M.N. [UNESP]; Santos, Taizha C. [UNESP]; Minto, Bruno W. [UNESP] (My University, 2007)
A 6-year-old male, Belgian shepherd dog was presented with lethargy, oliguria, hematuria, and reluctance to move. The dog developed hypertrophic osteopathy secondary to renal pelvis transitional cell carcinoma. A nephrectomy was performed and after a year, the dog was completely asymptomatic, and no evidence of metastatic disease was present.